2023
DOI: 10.3390/nu15020288
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus Intermittent Enteral Feeding in Critically Ill Children: A Systematic Review

Abstract: Administration of enteral nutrition (EN) in critically ill pediatric patients admitted to the pediatric intensive care unit (PICU) constitutes a major challenge due to the increased risk of complications, as well as the lack of well-trained healthcare professionals. EN is usually delivered via cyclic, continuous, or intermittent feeding; however, a number of potential barriers have been reported in the literature regarding different feeding regimens. The purpose of this review was to assess the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
4
0
2
Order By: Relevance
“…There was a large body of previous research describing the relationship between diet and the development of hypertension. Dietary plans such as the DASH and Mediterranean diets emphasize increased consumption of vegetables and fruits, a low‐sodium diet, and reduced fat intake to lower the risk of hypertension (Ahmed et al., 2020; Theodoridis et al., 2023). Hypertension affects 40% of the world's population and is an important risk for cardiovascular and cerebral disease in humans.…”
Section: Discussionmentioning
confidence: 99%
“…There was a large body of previous research describing the relationship between diet and the development of hypertension. Dietary plans such as the DASH and Mediterranean diets emphasize increased consumption of vegetables and fruits, a low‐sodium diet, and reduced fat intake to lower the risk of hypertension (Ahmed et al., 2020; Theodoridis et al., 2023). Hypertension affects 40% of the world's population and is an important risk for cardiovascular and cerebral disease in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Because the pH value in the stomach is not affected by eating, it can ensure effective blood perfusion of the gastrointestinal mucosa and prevent and cure intestinal bacterial translocation ( 47 ). However, some studies have found that intermittent feeding without infusion pump leads to a higher incidence of gastric tube dislocation, aspiration pneumonia, and abdominal distension than continuous infusion ( 48 , 49 ). Although there is no periodic fluctuation of gastrointestinal hormones during intermittent feeding, continuous enteral nutrition can maintain insulin, gastrin, and other gastrointestinal hormones at a high level, which is beneficial to intestinal absorption ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…A hipertensão arterial sistêmica (HAS) é na maioria das vezes é definida segundo a pressão arterial sistólica e/ou diastólica, acima de 140mmHg e 90mmHg, respectivamente (HONGXUAN, et al, 2020). De acordo com a Organização Mundial da Saúde, em torno de 50% de todos os adultos portadores de hipertensão arterial não foram ainda diagnosticados (THEODORIDIS, et al, 2023). Estima-se que 31,1% dos adultos tenham HAS.…”
Section: Introductionunclassified